2018
DOI: 10.1007/s00384-018-3107-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases in colorectal cancer: prognostic factors and survival analysis

Abstract: Time to BM diagnosis is shorter in RS CRC. The presence of two or more metastatic extracranial locations and progressive metastatic extracranial disease at the time of BM diagnosis could be bad prognosis factors for CRC BM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Previous studies have reported controversial results on surgery combined with radiotherapy for CRC patients with BM. 11 Some surgeons recommend surgery combined with radiotherapy as it improves CRC patient survival better than surgery only, and others found no differences between the two treatments. 12–14 Prospective studies including more samples should be carried out to assess treatments’ effectiveness and explore effective prognostic factors for CRC patients with BM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported controversial results on surgery combined with radiotherapy for CRC patients with BM. 11 Some surgeons recommend surgery combined with radiotherapy as it improves CRC patient survival better than surgery only, and others found no differences between the two treatments. 12–14 Prospective studies including more samples should be carried out to assess treatments’ effectiveness and explore effective prognostic factors for CRC patients with BM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported controversial results on surgery combined with radiotherapy for CRC patients with BM. 11 Some surgeons recommend surgery combined with radiotherapy as it improves CRC patient survival better than surgery only, and others found no differences between the two treatments. [12][13][14] Prospective studies including more samples should be carried out to assess Previous studies have explored factors associated with prognosis of CRC patients with BM, including extracranial metastases, number of BMs, and treatment of BM; 6,7,15,16 However, conclusions were varied among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…The smallest study population reported on five patients, while the largest study included 475 patients with BM. The analyzed studies are shown in Figure 6 and Table 7 [ 9 , 10 , 11 , 12 , 14 , 15 , 18 , 20 , 23 , 24 , 25 , 26 , 27 , 29 , 34 , 45 , 46 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four did not report the exact OS. Three focused on a specific metastatic site and five evaluated extracranial metastases in general; these included the studies by Quan et al (2020) (extracranial metastases: 4 months; no extracranial metastases: 6 months), Quan et al (2019) (extracranial metastases: 7 months; no extracranial metastases: 28 months), Del Carpio Huerta et al (extracranial metastases: 7.2 months; no extracranial metastases: 20.9 months), Gu et al (extracranial metastases: 7 months; no extracranial metastases: 13 months), and Noura et al (extracranial metastases: 8 months; no extracranial metastases: 24 months) [ 7 , 9 , 12 , 27 , 45 , 46 , 52 , 55 , 62 , 64 , 65 , 70 ]. Eleven studies reported multiple BM as a risk factor for poor OS.…”
Section: Resultsmentioning
confidence: 99%
“…CRC metastatic to the brain is a highly lethal condition warranting effective intervention (21), whereas the standard treatment modality for BM from CRC has not been established. Usually CRC-BM have been regarded as a terminal event which limited the development of treatment for colorectal cancer brain metastasis (22,23). Previous views hold that blood-brain barrier is considered to prevent most chemotherapy drugs from entering the brain and result in failure of chemotherapy in treatment of BM.…”
Section: Discussionmentioning
confidence: 99%